VISUALIZATION SHOTS PRAYING FARDHU USING MACROMEDIA DREAMWEAVER MX - Rokhani Rokhani; Ristyawati, SKom, MMSI Ristyawati, SKom, MMSI (Jurnal Sistem Informasi, 2006)
Visualization was praying fardhu using Dreamweaver MX as an editor in web design. Procedures described in this website fardhu following prayer after praying fardhu prayers in Arabic and translated, on every page there are pictures prayer guidance and explanation of the picture and accompanied by readings which must be pronounced when the movement takes place.